Retrospectroscope. The origin of electroshock therapy for treatment of psychiatric illnesses. - Geddes, L.A (IEEE Engineering in medicine and biology magazine)
There are several psychiatric illnesses that are difficult to treat with drugs. Among these are schizophrenia, manic depression, and profound depression; many of these may involve a tendency to suicide. In 1938 U. Cerletti conducted convulsive experiments on pigs using power-line current applied to electrodes at various sites. The effect of current duration was also investigated. As yet it is not known which areas in the brain are the optimum targets for the therapeutic use of cranially applied current to treat psychiatric illnesses, although the frontal lobes appear to be the best targets.